Project edPIRATE: A Teacher Residency MAT Program for Rural Educational Justice - Novak, Angela; Gallagher, Jennifer (Theory & Practice in Rural Education, 2024)
Rural educational justice demands reconstructing educational structures, including teacher preparation programs. With federal funding from a Teacher Quality Partnership grant, we rebuilt a Master of Arts in Teaching pathway program from the ground up, using a co-teaching residency model and a core framework of rural educational justice practices. With goals of establishing a healthy racial climate, building the racial literacy and culturally responsive teaching capacity of the teaching resident and mentor teacher teams, and fostering rural humanizing community spaces designed to cultivate genius, joy, love, intellect, and criticality (Muhammad, 2023), the first two years of the five-year grant are the subject of this theory-to-practice analysis. Utilizing a school-university-community collaboration approach, we identified, placed, supported, and mentored teacher residents in a place-conscious approach to the rural, racialized communities and contexts in which they teach. The purpose of this article is three-fold: (a) to contextualize the educational inequities and opportunities that exist in the rural Southeast Black Belt, (b) to present our rural educational justice teacher education framework, curriculum, and processes to members of the field of rural education, and (c) to share emerging themes from our experiences creating a teacher education program for rural educational justice. What we offer is not yet an exemplar. However, it provides theoretical foundations, an ambitious curricular framework for rural teacher education, and an analysis of lessons learned.